2012
DOI: 10.1179/1743294412y.0000000003
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterisation of nickel coated Ni-NCZ (nickel coated ZrO2) composite coating

Abstract: For the first time, electroless nickel plated ZrO 2 (Ni-NCZ) particles were used for the coelectrodeposition of Ni-NCZ composite coating. Optical microscope, SEM and X-ray diffraction studies showed that Ni-NCZ has a rough surface with a smaller Ni crystallite size than Ni-ZrO 2 due to the conductive properties of NCZ particles, which provide more nucleation sites for Ni clusters. The energy dispersive X-ray spectroscopy measurement results showed that Ni-NCZ has more co-electrodeposited particles than Ni-ZrO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…2, the optical microscope images from surface morphologies and cross sections of the electroplated composite coatings have been shown. It must be reminded that the coatings have been coelectrodeposited in an applied magnetic field of 0.05 T. In previous work [29], NCZ particles used to produce Ni-NCZ composite coating and it has been shown that no significant increase occurred in the amount of incorporated particles (as compared to Ni-ZrO 2 ) but surface morphology became rough due to the electrical conductivity of the NCZ particles. No magnetic field was applied in that work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2, the optical microscope images from surface morphologies and cross sections of the electroplated composite coatings have been shown. It must be reminded that the coatings have been coelectrodeposited in an applied magnetic field of 0.05 T. In previous work [29], NCZ particles used to produce Ni-NCZ composite coating and it has been shown that no significant increase occurred in the amount of incorporated particles (as compared to Ni-ZrO 2 ) but surface morphology became rough due to the electrical conductivity of the NCZ particles. No magnetic field was applied in that work.…”
Section: Resultsmentioning
confidence: 99%
“…But NCZ particle has conductive properties (covered with electroless Ni-P coating) so that when this particle is entrapped into the growing electrodeposited Ni coating, the Ni clusters will nucleate on the surface of the particle and the coating will cover the particle so that the surface morphology will be rough (Fig. 3b) [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ZrO 2 particles are successfully incorporated into matrices such as Ni. [3][4][5], Cu [6], Zn [7] and Co [8]. In all cases ZrO 2 improves both mechanical (microhardness, wear resistance) and corrosion resistance properties of the coatings.…”
Section: Introductionmentioning
confidence: 98%